Vzaimosvyaz reologicheskikh svojstv krovi s parametrami lipidnogo profilya u sportsmenov - Melnikov, A. A.; Vikulov, A. D. (Teorija i Praktika fiziceskoj Kul'tury, 2002)
The purpose of this paper was to find the interrelations between rheologycal properties of the blood and the lipids' structure in athletes. The research was carried out on 15 athletes engaged in kinds of sports with primary development of endurance (track and field athletics, ski races, bicycle races). Their qualification was candidate in master of sports and master of sports. They were aged 18-21. The control group included practically healthy persons with the same age who were not engaged in sports. The carried out research has shown, that at the surveyed athletes observably positive reorganizations of the lipids' structure are connected with rheologycal properties of blood: the deformability and aggregation of erythrocytes. The increase of the deformability and the decrease of aggregation of erythrocytes appreciably promote to the oxygen transport function of the blood at the level of microcirculation and to increase the functionalities of the trained organism.